Development and Acceptance of Healthy and Balanced Diet for Diabetes Mellitus Patients among UKM Staff Using Linear Programming - Khashim, Shirin; Rajikan, Roslee (Pakistan Journal of Nutrition, 2019)
Background and Objective: It is established that nutrition and diet management is a significant aspect of managing diabetes. The aim of this study was to construct a balanced, palatable and affordable diet that helps diabetics in Malaysia to manage their disease. Linear programming techniques were employed to develop a menu plan that takes into account not only nutritional guidelines but also palatability and budget constraints. Materials and Methods: A cross-sectional study involving 120 UKM staff aged 30-59 years old diagnosed with Type 2 Diabetes Mellitus (T2DM) was conducted. Socio-demographic, anthropometry, dietary intake and food security and the subjects’ glucose level (HbA1c) were taken in the first phase. Three diet models were produced: Model 1 is 1391.419 kcal day–1 costing RM 9.94; Model 2 is 1523.500 kcal day–1 at RM9.23 and Model 3 is 1713.500 kcal day–1 at the lowest cost of RM 9.17. These three diabetes diet management models were tried out among ten randomly selected subjects. All data collected were analysed using the Statistical Package for Social Sciences (SPSS) program version 22.0. Results: No significant difference was found between groups within each socio-demographic characteristic, comparing HbA1c levels among the subjects but significant differences were found in the nutrient intakes between male and female subjects in the mean daily intakes of energy, carbohydrates, fat and sucrose but not in crude fibre and protein. These data were needed to develop a healthy and balanced menu at a minimum cost via linear programming for the second phase. Results showed a significant improvement in both weight loss (p = 0.029) and HbA1c control (p = 0.028) as evidenced by data collected pre and post-diet implementation. Conclusion: Linear programming can be an effective tool in helping to produce an optimised healthy and balanced diet at minimal cost by interpreting and translating dietary recommendations into a nutritional model, based on local market prices.